What Do Values Have to Do With It?: Resilience of Two Types of Farmers in Hawai‘i to the COVID-19 Pandemic - Hutchins, Leslie; Feldman, Mackenzie (Frontiers in Sustainable Food Systems, 2021)
A history of agriculture and socio-cultural formation has led to a complex local food system in Hawaiʻi. Customary agricultural systems built by Kanaka Maoli (native Hawaiians) are now rested within a landscape filled with many different crops tended by farmers from a variety of ethnic backgrounds. Value systems dictating farming practices and crop selling decisions differ. In Hawai’i, values of food security or food sovereignty are of particular importance, especially as growing movements seek to increase local production and decrease the state’s reliance on imported food in the wake of the COVID-19 pandemic. In this study, we systematically compare two different groups of farmers in Hawai’i and their values related to production and distribution. We then analyze the experiences of these two groups of farmers during the COVID-19 pandemic and their responses to them. The study is based on interviews with 22 Kanaka Maoli (KF) and Non-Kanaka Maoli local farmers (LF) from the island of O’ahu. Ninety percent of KF say values associated with both food security and sovereignty drive their production and distribution decisions, while 75 percent of LF describe food security as the sole driver. Sixty percent of HF follow a non-profit economic model and emphasize cultural and educational values in their production decisions. LF follow profit-driven models and emphasize the influence the market has in their decisions. Prior to the COVID-19 pandemic, KF sold or donated the bulk of their crops to the local community through farm pickups, while restaurants were the primary buyers of LF crops. During the pandemic, the local community continues to be the primary recipient for HF, and due to the closure of many restaurants, LF have pivoted their sales to the community as well. Farmer interviews are augmented by three interviews with Hawai’i food system experts and relevant literature to suggest multiple pathways state agencies and local organizations could implement to support farmers from different backgrounds through COVID and into the future.